ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERKEMBANGAN MOTORIK KASAR PADA BATITA DI WILAYAH KERJA PUSKESMAS MEUREUDU KECAMATAN MEUREUDU KABUPATEN PIDIE JAYA - Usrati, Savira; Santi, Tahara Dilla; Amin, Fauzi Ali (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
The purpose of this study is to determine the analysis of factors related to gross motor development in toddlers in the Meureudu Health Center Working Area, Meureudu District, Pidie Jaya Regency in 2022. This research is descriptive analytic with a cross-sectional research design. Data collection is carried out by distributing questionnaires. The population in this study was all toddlers as many as 99 people and a sample of 99 toddlers with a sampling technique, namely Total Sampling. The data analysis used is univariate and bivariate with the statistical test used, namely the Chi-Square test. The results showed that there is a relationship between gross motor development and maternal knowledge (p value 0.002), there is a relationship between gross motor development of parenting (p value 0.001), there is a relationship between gross motor development and nutritional status (p value 0.002), there is a relationship between gross motor development and birth weight (p value 0.007) and there is a relationship between gross motor development and a history of breastfeeding (p value 0.002) gross motor development. It is hoped that toddler mothers will increase knowledge and motivation by digging up information about gross motor development from various sources such as from health workers and books, so that mothers can supervise gross motor development.